Peran Grit dan Trust in organization dalam Meningkatkan Task performance Karyawan di ZOOM Hotel Mulawarman Samarinda - Arinil Hidaya; Robiansyah Robiansyah (INDO PUBLISHING, 2026)
This study aims to determine the effect of grit and trust in organization on employee task performance at Zoom Hotel Mulawarman Samarinda. The independent variables in this study are grit and trust in organization, while the dependent variable is employee task performance. The research method used is a quantitative approach, with data collected directly through the distribution of questionnaires to 40 hotel employees. Instrument testing was carried out with validity and reliability tests, and data analysis was conducted using multiple linear regression with the assistance of SPSS Statistics 22 software. The results show that grit has a positive but not significant effect on task performance, while trust in organization has a positive and significant effect on employee task performance at Zoom Hotel Mulawarman Samarinda.